A Juridical Analysis of the Welfare of Civil Servant Medical Personnel in Remote Areas of Indonesia - Ramadhania, Nadira Wahyu; Noor, M. Tauchid; Sulakson, Sulakson (Institute for Law and Economics Studies, 2025)
This study examines the welfare of medical personnel serving as Civil Servants (PNS) under the Indonesian civil service system, particularly those assigned to remote areas. Employing a normative juridical method with both a statute approach and a conceptual approach, this research explores the government’s responsibility to guarantee fair welfare and evaluates the adequacy of the existing legal framework. Legal materials were collected through literature study and analyzed using prescriptive legal analysis. Statistical data indicate an uneven distribution of health workers, with more than 60% concentrated in Java–Bali, whereas remote, border, and island regions continue to face critical shortages. Relevant legal instruments, including Law Number 20 of 2023 on the State Civil Apparatus and Law Number 17 of 2023 on Health, establish the legal basis for civil servant welfare. Nevertheless, normative gaps remain, particularly regarding technical arrangements such as incentive amounts, distribution mechanisms, and employment security guarantees. The findings reveal that current welfare protections for medical civil servants in remote areas are not yet fully effective, underscoring the need for more detailed derivative regulations to ensure legal certainty, distributive justice, and equitable deployment. The research contributes to legal scholarship by identifying shortcomings in the existing framework, offering policy recommendations for more comprehensive and enforceable welfare protections, and highlighting the importance of aligning normative guarantees with operational realities to strengthen the welfare state in Indonesia. However, this study is limited to normative legal analysis and does not include empirical data on implementation or the lived experiences of medical staff.